¿Era Pedro de Valencia desdendiente de judeosconversos? (Estudios humanísticos. Geografía, historia y arte, 1995)
This study wonders about the possible Jewish ancestry of the well known humanist Pedro de Valencia. In absence of documents which answer this question, present a serie of facts related to bis life which, according to the author, give many possibilities for an affirmative answer. The facts studied are all related to his family antecedents, the early years of bis life, his studies in Salamanca, his marriage to his cousin Inés de Ballesteros, his intellectual curiosity and friends. His "converso" origin in now a hypothesis which propably Jets us interpret the life and thought of one of the most important characters from the Spanish Golden Century better.